La riforma scolastica in Lombardia tra XVIII e XIX secolo - Piseri, Maurizio (Studi sulla Formazione/Open Journal of Education, 2025)
The foundation of the public primary school system of Austrian Lombardy involved two steps: the 1775 reform and the 1786 reform. Recent studies have underlined the continuity in the proceeding of the two reforms. In this way it is possible to circumscribe the breaking points to merely didactic and administrative aspects. Based on the uniformity of didactics, the normal method required a net of school inspectors to monitor the activity of the schools as well as the creation of training courses for the education of teachers. Even though the normal method had been deeply reformed in Austria after 1780, it was rigorously applied in its orthodox version in the Lombard schools until 1791. From 1791 the method was revised, just like in Vienna ten years before, under pressure from politicians, intellectuals and the families themselves. The two steps of the path of the normal schools in Lombardy reflect the position of the two main protagonists in the Lombard school system: Wolfgang Moritz, a supporter of the Felbiger’s method, and Giovanni Bovara, the mind behind the 1775 reform and a critic of the new didactics in relation to those parts perceived as mechanical and mnemonic.